Determining non-radiative decay rates in TADF compounds using coupled transient and steady state optical data. Issue 12 (14th February 2022) - Sem, Stefano; Jenatsch, Sandra; Stavrou, Kleitos; Danos, Andrew; Monkman, Andrew P.; Ruhstaller, Beat
Abstract : Understanding the role of non-radiative decay rates in TADF OLEDs by comparing PLQY and ELQY simulated values. Quantification of the non-radiative decay rates in TADF compounds with a sophisticated fitting procedure. Abstract : Thermally-activated delayed fluorescence (TADF) compounds are promising materials used in emissive layers of organic light-emitting diodes (OLEDs). Their main benefit is that they allow the internal quantum efficiency of the OLED to reach up to 100% by converting non-radiative triplet states into radiative singlets. Besides the importance of having a high reverse intersystem-crossing rate, which governs triplet conversion, minimizing the non-radiative decay processes is also extremely important to reach high efficiency. In this study we provide a new method to quantify not only the most important decay rates involved in the TADF process, but also the non-radiative decay rates of both singlet and triplet states individually from transient and steady state experimental optical data. In addition, the different contribution that the two non-radiative decay pathways have on the internal quantum efficiency is investigated. Finally, the method is applied to experimental data from two TADF materials.